2021
DOI: 10.1186/s13287-021-02282-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from miR-26a-modified MSCs promote axonal regeneration via the PTEN/AKT/mTOR pathway following spinal cord injury

Abstract: Background Exosomes derived from the bone marrow mesenchymal stem cell (MSC) have shown great potential in spinal cord injury (SCI) treatment. This research was designed to investigate the therapeutic effects of miR-26a-modified MSC-derived exosomes (Exos-26a) following SCI. Methods Bioinformatics and data mining were performed to explore the role of miR-26a in SCI. Exosomes were isolated from miR-26a-modified MSC culture medium by ultracentrifugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 94 publications
2
40
0
Order By: Relevance
“…Several studies reported intravenous administration of the same dose of exosomes (100 μg, 200 µg). The studies used many different miRNAs to modify exosomes, including miR-26a ( Chen et al, 2021 ), miR-126 ( Huang et al, 2020 ), miR-145-5p ( Jiang and Zhang, 2021 ), miR-381 ( Jia et al, 2021 ), miR-21 ( Ji et al, 2019 ; Kang et al, 2019 ), miR-216a-5p ( Liu et al, 2020 ), miR-421-3p ( Wang et al, 2020 ), miR-29b ( Yu et al, 2019 ) and miR-181c ( Zhang M. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported intravenous administration of the same dose of exosomes (100 μg, 200 µg). The studies used many different miRNAs to modify exosomes, including miR-26a ( Chen et al, 2021 ), miR-126 ( Huang et al, 2020 ), miR-145-5p ( Jiang and Zhang, 2021 ), miR-381 ( Jia et al, 2021 ), miR-21 ( Ji et al, 2019 ; Kang et al, 2019 ), miR-216a-5p ( Liu et al, 2020 ), miR-421-3p ( Wang et al, 2020 ), miR-29b ( Yu et al, 2019 ) and miR-181c ( Zhang M. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Li ( Li S.-P. et al, 2018 ) found that rats that received miR-133-modified exosomes recovered well, and that these exosomes promoted axon growth and reduced the levels of RhoA protein in the injured spinal cord, indicating that RhoA is a direct target of miR-133, and suggesting that the RhoA/ROCK signaling pathway plays a critical role in spinal cord neuron death after acute SCI ( Wu et al, 2017 ). Chen found that exosomes derived from miR-26a-modified MSCs activate the PTEN-AKT-mTOR pathway, and promote axon regeneration and neurogenesis, and reduce glial scar formation in SCI( Chen et al, 2021 ). Our current meta-analysis findings suggest that miRNA-modified exosomes can significantly improve motor function in the rodent SCI model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the early stage of SCI, if one can effectively reduce neuronal cells apoptosis, promote vascular remodeling, stimulate neuronal regeneration, promote axon regeneration, regulate microglial activation, and inhibit inflammation, it is possible to effectively slow down the process of SCI and improve the prognosis of SCI patients. Because of the presence of various therapeutic growth factors and miRNAs in exosomes (Tomasoni et al, 2013;Anderson et al, 2016;Chen et al, 2021), in recent years, many studies have reported that exosomes have shown therapeutic effects on CNS diseases, including SCI (Table 1 and Figure 3).…”
Section: Exosomes: Applications In Scimentioning
confidence: 99%
“…MiR-155 resulted in improved regeneration and functional recovery after spinal cord dorsal column injury, effects that appear to be mediated through the reduced inflammatory response as well as induction of regeneration-associated genes [ 93 ]. miRNA-26a primed mesenchymal stem cells were shown to promote spinal cord repair through the mTOR pathway [ 94 ], and miR-20a and miR 155-5p promotes the growth of injured sensory axons in the spinal cord dorsal column via the cAMP/PKA [ 95 ] and PDZ-RhoGEF/RhoA/GAP43 [ 96 ] pathways, respectively. Non-coding RNAs have also been implicated in neuropathic pain [ 97 , 98 ], a common, severely disabling sequelae of spinal root or spinal cord lesion.…”
Section: Regulating Gene Expression After Axon Injurymentioning
confidence: 99%